Used cooking oil as a source for biodiesel blend - Samsuri, A. (Faculty of Chemical and Natural Resource Engineering, 2008)
With the depleted world petroleum reserves and increase demand for oil as a fuel, it has become imperative to investigate the possibility of using non-fossil fuel as an alternative fuel for diesel engine. Therefore, this paper describes the experimental investigation on possibility of producing biodiesel from used cooking oil and their properties, characteristics and performance as a blended biodiesel for diesel engine at constant speed. Properties analysis of biodiesel from used cooking oil in accordance to the ASTM D6751 specification showed that it fulfilled the requirements of a biodiesel fuel specification. Comparison also conducted between the ordinary diesel as a standard fuel and several set of blended biodiesel range from I% to 5% volume of biodiesel. The properties of blended biodiesel were not much different to the properties of conventional diesel fuel except the density and specific gravity. The density of diesel is 0.8358 gm/cc and the biodiesel is 0.8723 gm/cc. For blended biodiesel, it's slightly increased from 0.8363 gm/cc for I% to 0.8385 gm/cc for 5%. The results from Detroit Deisel Engine performance test showed that the blending fuel sample produced almost the same performance characteristics as compared to conventional diesel. As a result, blended biodiesel with used cooking oil is suitable to be used up to 5% as a fuel for diesel engine at constant speed and gives the same engine performances as conventional diesel fuel